ANALYZING THE READINESS FOR RETIREMENT BETWEEN MALE AND FEMALE IN CIVIL SERVANT AT BKPSDM TALAUD - Amisi, Anita Selyn; Saerang, David P.E.; Tumewu, Ferdinand J. (Universitas Sam Ratulangi, 2019)
Abstract: As retirement is mostly experienced by all employees, the readiness to face the circumstance is urgently needed to survive the life subsequently. In fact, the employeesâ€™ orientations in their gender role, which is naturally diverse in the characteristics, influence the various state of the employee readiness. This study aims to determine the significance of the differences between male and female in civil servants at BKPSDM Talaud. Respondents in this study were 50 male 50 female and the sampling technique used was random sampling. The research method used in data collection is by using the Likert scale method, namely the scale of pension readiness which is made based on aspects of pension readiness developed based on the theoretical views of Sutarto and Ismulcokro. The data analysis technique used is the t-test analysis. From the results of data analysis obtained a significance value of 0.001 (p> 0.05) which means the difference in readiness between men and women Talaud BKPSDM employees. Employees who are entitled to receive good compensation from men and women who both maintain acceptable money so they can adjust to the good when retirement arrives. Employees especially those who are about to retire are expected to need to prepare not only externally but also internally. The external factors consist of many things such as financial, physical, post-retirement activities, environment and others. While in internal factors there are mental and psychological conditions.Â Keywords: readiness for retirement, compensation, gender